2021
DOI: 10.1016/j.jbc.2021.101341
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization state affects lipid composition and the channeling of exogenous fatty acids into endogenous lipid pools

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…We and others have previously shown that M[LPS] up-regulate de novo lipogenesis to supply new FA for phospholipid synthesis. 4,10 There is now evidence to support a role for both exogenous FA uptake, 11,12 as well as de novo lipogenesis in M[IL-4]. 51 Despite the potentially divergent sources of FA, differences in the side chain composition of choline-containing phospholipids between macrophage polarizations may fuel distinct lipid signaling pathways following phospholipase-specific processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that M[LPS] up-regulate de novo lipogenesis to supply new FA for phospholipid synthesis. 4,10 There is now evidence to support a role for both exogenous FA uptake, 11,12 as well as de novo lipogenesis in M[IL-4]. 51 Despite the potentially divergent sources of FA, differences in the side chain composition of choline-containing phospholipids between macrophage polarizations may fuel distinct lipid signaling pathways following phospholipase-specific processing.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent lipidomic analyses of cultured macrophages demonstrated sweeping alterations to phospholipid composition and content in response to various inflammatory stimuli. 4,[10][11][12] To begin to address the specific roles of choline as a regulator of macrophage functions, we and others have shown that polarization with the bacterial endotoxin lipopolysaccharide (LPS; termed M[LPS]) in primary mouse macrophages leads to increased choline uptake and PC synthesis in an Slc44a1-dependent manner. 4 While inhibiting choline uptake and metabolism led to more pronounced inflammatory responses in M[LPS], whether choline metabolism is regulated and how it may alter macrophage phenotype in response to Th2 cytokine exposure remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Later in life, ATMs perform contrasting roles, as they maintain metabolic homeostasis, but also contribute to the aetiology of obesity through non-resolving inflammation ( Morgan et al, 2021 ). Progressive lipid accumulation within macrophages drives a switch between the polarization of anti-inflammatory M2 ATMs to pro-inflammatory M1 ATMs ( Prieur et al, 2011 ).…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…In the setting of obesity, M2 ATMs are critical for the removal of necrotic-like adipocytes, as well as facilitating lipid storage in WAT ( Cinti et al, 2005 ; Cox et al, 2021 ). A recent study revealed that treatment of M1 and M2 bone marrow-derived macrophages (BMDM) with exogenous fatty acids caused an increase in TG and cholesterol ester (CE) species in M1 macrophages, whilst a greater increase in PE and PC ether lipids was observed in M2 macrophages ( Morgan et al, 2021 ). Mechanistically, M2 macrophages express higher levels of Gnpa t and Far1 , the enzymes involved in the first and rate limiting steps of endogenous ether lipid synthesis, respectively ( Jha et al, 2015 ).…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Notably, each leukocyte class can be distinguished by specific fatty acid profiles, likely influencing lipid rafts, whereas it is unclear how these processes vary amongst distinct subclass phenotypes within immune cell populations [ 56 ]. A lipidomic study indeed revealed that fatty acid processing and lipid composition differs amongst macrophage subtypes (M1 vs. M2) with a quantified increase in exogenous fatty acid channeling into sphingolipids in M2 macrophages [ 57 ]. Thus, taking into account the various activation states and motions an immune cell undergoes, an axis-polarized phenotypic distinction (stage of recruitment, uropodia/lamellipodia formation) can emerge.…”
Section: Mechanisms Of Immune Cell Phenotype Switching: Outside In An...mentioning
confidence: 99%